Association of Fetal Fraction of Cell-Free DNA and Hypertensive Disorders of Pregnancy - Bender, Whitney R.; Koelper, Nathanael C.; Sammel, Mary D.; Dugoff, Lorraine (American Journal of Perinatology, 2019)
Objective The objective of this study is to examine the relationship between fetal fraction and hypertensive disorders of pregnancy.Study Design This is a retrospective cohort study of women with singleton pregnancies who had cell-free DNA (cfDNA) screening at 10 to 20 weeks of gestation. The primary outcome was the development of gestational hypertension (gHTN), preeclampsia (PEC), and PEC with severe features. Multinomial logistic regression was performed to assess the relationship between fetal fraction and pregnancy outcomes of interest while controlling for potential confounders.Results Among 2,701 women meeting inclusion criteria, 387 (14.3%) were diagnosed with hypertensive disorders of pregnancy. First-trimester fetal fraction was significantly lower in women diagnosed with hypertensive disorders of pregnancy (10.9 vs. 12.4, p < 0.0001). An increased risk of gHTN and PEC, PEC with severe features with delivery > 34 weeks, and PEC with severe features with delivery ≤ 34 weeks was seen with lower first-trimester fetal fractions (odds ratio [OR]: 0.55, 95% confidence interval [CI] [0.36–0.83], p = 0.005; OR: 0.59, 95% CI [0.35–0.99], p = 0.048; and OR: 0.27, 95% CI [0.08–0.96], p = 0.044). The relationship between fetal fraction and hypertensive disorders of pregnancy was not statistically significant after adjusting for maternal age, race, body mass index, and chronic hypertension.Conclusion Fetal fraction of cfDNA at 10 to 20 weeks of gestation was not associated with the development of hypertensive disorders of pregnancy.
Keywords: cell-free DNA; fetal fraction; pregnancy; hypertension; preeclampsia